Strengthening Local Values in Shadow Puppet Messages at Padepokan Sehat Medika, Kebumen - Mukti, Anjar; Hendrayani, Yani; Irawati, Aniek (UPT Publikasi Ilmiah UNISBA, 2024)
Shadow puppet shows, as part of traditional culture, do not only function as entertainment with aesthetic value. The Shadow puppet show is a traditional communication medium containing implied and explicit messages. The messages in the shadow puppet show are generally about the values of life used for moral growth in society. This study aimed to discover the messages in the shadow puppet show at Padepokn Sehat Medika, Kebumen Regency. The researcher tried to examine the message's meaning from one of the stories in the shadow puppet show at Padepokan Sehat Medika, Kebumen Regency, namely Wahyu Tejaningrat, focusing on the meaning contained in the story. The research paradigm used is constructivism, with qualitative methods and content analysis approaches. The theory used is Paul Ricoeur's Hermeneutics model, a theory regarding the rules of interpreting specific texts, signs, or symbols with the essence of meaning. The researcher found that the story has a profound message about leadership and the role of society in government that can educate and make people aware of the current conditions in society.